Microplastic abundance in blood cockles and shrimps from fishery market, Songkhla Province, Southern Thailand - Goh, Patricia Blair; Siriporn Pradit,; Prawit Towatana,; Somkiat Khokkiatiwong,; Butchanok Kongket,; Hwei, Julia Zhong Moh (Penerbit Universiti Kebangsaan Malaysia, 2021)
Microplastics have been one of the major pollutants in the marine environment throughout the recent decade. At present, microplastic contamination in marine ecosystems of Thailand region has become an increasing environmental concern because the ingestion of microplastics in marine organisms may adversely influence the safety of seafood. Cockles and shrimps widely distribute among marine organisms in Thailand since they are one of the commercial sources of seafood, which may be a route of exposure to microplastics towards human. This study documents a market survey in order to understand the extension of microplastic presence in blood cockles (Anadara granosa), fine shrimp (Metapenaeus elegans) and Indian white shrimp (Fenneropenaeus indicus) sold in the fishery market in Singhanakorn district, Songkhla province. These selected species are widely consumed and economically important, especially in the southern Thailand region. The total microplastic concentration in blood cockles is 4.71±0.06 n/g (wet weight) and 2.64±0.01 n/individual; in fine shrimp is 0.50±0.19 n/g (wet weight) and 3.70±1.12 n/individual; in Indian white shrimp is 0.69±0.48 n/g (wet weight) and 3.45±0.04n/individual. Discovered microplastics in all the species samples were mainly composed of microplastic fibres and black colour was found to be more predominant. Our results indicate that microplastic contamination is present in Thailand’s commercial seafood species. As microplastic able to be transferred to human through food web, we suggest further market-based survey studies on other seafood sources.